Cation depletion by the sodium pump in red cells with pathologic cation leaks. Sickle cells and xerocytes. - Joiner, C H (1986)
The mechanism by which sickle cells and xerocytic red cells become depleted of cations in vivo has not been identified previously. Both types of cells exhibit elevated permeabilities to sodium and potassium, in the case of sickle cells, when deoxygenated. The ouabain-insensitive fluxes of sodium and potassium were equivalent, however, in both cell types under these conditions. When incubated 18 hours in vitro, sickle cells lost cations but only when deoxygenated. This cation depletion was blocked by ouabain, removal of external potassium, or pretreatment with 4,4'-diisothiocyanostilbene-2,2'-disulfonate, which blocks the increase in cation permeability induced by deoxygenation. The loss of cation exhibited by oxygenated xerocytes similarly incubated was also blocked by ouabain. These data support the hypothesis that the elevated "passive" cation fluxes of xerocytes and deoxygenated sickle cells are not directly responsible for cation depletion of these cells; rather, these pathologic leaks interact with the sodium pump to produce a net loss of cellular cation.